Strategi Pengendalian Suplai Air Bersih di PT. Semen Padang dengan Pemanfaatan Level Switch dan Siklus PDCA - Refki Budiman; Queen Hesti Ramadhamy; Baik Budi; Jhonny Faizal (Jurnal Andalas: Rekayasa dan Penerapan Teknologi, 2025)
Water Plan (WP) is a clean water treatment unit that supplies water for residential areas, offices, and factory operations at PT Semen Padang. One of the main issues faced by WP is the low water level in the canal due to inadequate monitoring by operators, which can lead to operational disruptions and even production shutdowns. This study aims to develop a clean water supply control strategy by implementing an automatic monitoring system using a level switch based on the Plan-Do-Check-Action (PDCA) cycle. The research method begins with problem identification through an analysis of the operator's logbook, followed by determining priorities and root causes using the Strategic Risk Severity Matrix and the Nominal Group Technique (NGT). Improvement implementation is carried out by installing a level switch and an alarm in the operator room to ensure automatic water level monitoring. The evaluation results indicate a significant improvement in water supply quality, a reduction in operational disruption risks, and maintenance cost efficiency, with potential water savings reaching 450,000 m³ per month and a reduction in pump repair costs of Rp. 25,000,000. The implementation of this PDCA-based system has proven effective in enhancing the reliability of the clean water supply and supporting continuous improvement in WP PT Semen Padang. In the future, a similar approach can be applied to optimize water resource management in other industrial sectors.